TEACHERS' INNOVATIVE STRATEGIES IN DEVELOPING CONTEXTUAL INTEGRATED SOCIAL STUDIES LEARNING IN MI/SD - Putri Rahma Dani; Aramudin (Universitas Islam Negeri Mataram, 2025)
This study aims to describe innovative strategies used by teachers in developing contextual integrated social studies learning in MI/SD, including the planning, implementation, and assessment stages, as well as the factors that support and hinder its implementation. The research used a descriptive qualitative approach with a case study design at SDN 001 Airtiris. The research subjects included classroom teachers, the principal, and students as supporting informants. Data were collected through observation, in-depth interviews, and documentation studies, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the teachers' strategies were realized through mapping the integration of social studies concepts based on the local context, implementing meaningful learning activities such as discussions and simple social problem solving, and using authentic assessments in the form of assignments, work demonstrations, and reflections. Supporting factors included the support of the principal and the use of the environment as a learning resource, while time and facility constraints were the main obstacles. This study provides practical recommendations for MI/SD teachers in developing contextual and meaningful integrated social studies learning.